Organizational Characteristics and Readiness for Tobacco-Free Workplace Program Implementation Moderates Changes in Clinician's Delivery of Smoking Interventions within Behavioral Health Treatment Clinics. Issue 2 (24th August 2020) - Nitturi, Vijay; Chen, Tzu-An; Kyburz, Bryce; Martinez Leal, Isabel; Correa-Fernandez, Virmarie; O'Connor, Daniel P; Williams, Teresa; Garey, Lorra; Stacey, Tim; Wilson, William T; Lam, Cho; Reitzel, Lorraine R
Abstract: Background: Smoking is elevated amongst individuals with behavioral health disorders, but not commonly addressed. Taking Texas Tobacco Free is an evidence-based, tobacco-free workplace program that addresses this, in-part, by providing clinician training to treat tobacco use in local mental health authorities (LMHAs). This study examined organizational moderators of change in intervention delivery from pre- to post-program implementation. Methods: LMHA leaders completed the Organizational Readiness for Implementing Change (ORIC) and provided organization demographics pre-implementation. Clinicians ( N = 1237) were anonymously surveyed about their consistent use of the 5As (Asking about smoking; Advising clientele to quit; Assessing willingness to quit; Assisting them to quit; Arranging follow-up) pre- and post-program implementation. Adjusted generalized linear mixed models were used for analyses (responses nested within LMHAs), with interaction terms used to assess moderation effects. Results: Clinician delivery of 5As increased pre- to post-implementation ( p < .001). LMHAs with fewer employees (ref = ≤300) demonstrated greater increases in Asking, Assessing, and Assisting over time. LMHAs with fewer patients (ref = ≤10 000) evinced greater changes in Asking over time. Less initial ORIC Change Efficacy, Change Commitment, and Task Knowledge were each associated with greater pre- to post-implementation changes in Asking. Less initial Task Knowledge was associated with greater increases in Advising, Assessing, and Assisting. Finally, less initial Resource Availability was associated with greater increases in Assisting (all moderation term p s < .025). Conclusion: The smallest and least ready LMHAs showed the largest gains in tobacco cessation intervention delivery; thus, low initial readiness was not a barrier for program implementation, particularly when efficacy-building training and resources are provided. Implications: This study examined organizational moderators of increases in tobacco cessation treatment delivery over time following the implementation of a comprehensive tobacco-free workplace program within 20 of 39 LMHAs across Texas (hundreds of clinics; servicing >50% of the state) from 2013 to 2018. Overall, LMHAs with fewer employees and patients, and that demonstrated the least initial readiness for change, evinced greater gains in intervention delivery. Findings add to dissemination and implementation science by supporting that low initial readiness was not a barrier for this aspect of tobacco-free workplace program implementation when resources and clinician training sessions were provided.